Kinnow Mandarin enriching citrus industry - Kumar, Sunil; Awosthi, O P; Singh, Awtar (Indian Horticulture, 2019)
Kinnow mandarin, a hybrid between King orange and Willow leaf mandarin which could not become very popular in the USA, has revolutionized the citrus industry in India, Pakistan and Bangladesh owing to its profuse bearing, attractive orange-coloured fruits, high juice content, better yield and quality. The vitamin C content is 31mg/100ml juice. In India, it is commercially grown in the arid and semi-arid regions and has adapted very well in Sri Ganganagar district of Rajasthan, parts of Punjab, Haryana and foothills of Himachal Pradesh. In the recent past, due to its profuse bearing, high quality fruit and higher economic returns besides the traditional areas, there had been a rapid expansion in area under Kinnow around NCR region of Delhi, Western Uttar Pradesh, Nagpur and Akola regions of Maharashtra including tribal tracts of Chhattisgarh and Madhya Pradesh. The Kinnow industry in India can be further revolutionized by refinement of production technologies such as selection of appropriate rootstocks, quality planting material, irrigation scheduling, integrated crop management practices and post harvest handling.